Development of Science Literacy Through Group Choice STEM-PjBL Projects Integrated with Matter State Changes - Rahadian Sujud; Yuli Rahmawati; Ade Dwi Utami (Jurnal Penelitian Pendidikan IPA, 2024)
This research focuses on the development of students' science literacy in the topic of matter state changes at the primary school level. It utilizes Science, Technology, Engineering, and Mathematics - Project-Based Learning (STEM-PjBL) as a holistic integrative learning approach, supporting 21st-century skills. The meaningful learning design is crafted to help students understand the material while applying their understanding to a simple project appropriate for primary school students' cognitive levels. The study was conducted in a fifth-grade class at an educational unit in Tangerang City, Banten Province, Indonesia. Using a qualitative research method, data was collected through interviews, observations, reflective journals, and researchers' notes. The STEM-PjBL learning stages included reflection, research, discovery, application, and communication. The Shwartz assessment was developed as an instrument to evaluate students' science literacy abilities. The results show that implementing the STEM-PjBL approach promotes student-centered learning, builds group cooperation, is enjoyable, and develops students' science literacy. Students worked in groups on their chosen projects related to the topic of matter state changes. The average project score for each group received an A rating in completing the STEM-PjBL project. Interdisciplinary learning can encourage students to understand the characteristics and concepts of a theory and relate them to everyday life, thereby impacting their understanding and project development.